2018
DOI: 10.2355/isijinternational.isijint-2018-169
|View full text |Cite
|
Sign up to set email alerts
|

Transient Thermo-fluid and Solidification Behaviors in Continuous Casting Mold: Oscillation Behaviors

Abstract: A computational model of the continuous casting process has been developed, which includes transient heat transfer, multiphase flow, solidification, and mold oscillation. Succeeding the previous report on the evolution phenomena in the mold, this article describes fluctuations in the pressure, heat flux, and slag films during the oscillation cycle and the coupling effect of these variables on slag flow and shell growth. The results show that the predicted flux pressure is decided by the combined effect of mold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The air part is divided into tetrahedral meshes, and the rest into hexahedral meshes. [10,11,13,15,21,25] To investigate the influence of the stirrer position on multiple physical fields behaviors in billet continuous casting process, the stirrer center position is moved from Y ¼ 515 to Y ¼ 815 mm, as shown in Figure 1b.…”
Section: Homogeneous Modelmentioning
confidence: 99%
“…The air part is divided into tetrahedral meshes, and the rest into hexahedral meshes. [10,11,13,15,21,25] To investigate the influence of the stirrer position on multiple physical fields behaviors in billet continuous casting process, the stirrer center position is moved from Y ¼ 515 to Y ¼ 815 mm, as shown in Figure 1b.…”
Section: Homogeneous Modelmentioning
confidence: 99%
“…[18][19][20] However, the solid-shell unevenness may not precisely coincide with Φ q of the mold, 21) because both phenomena are also affected by other factors including casting speed 21,22) superheat, 4,23) mold lubricant, 3,18,24,25) oscillation conditions and moldlevel fluctuation. 3,21,26,27) Some researchers have attempted to quantify the unevenness of solid-shell by measuring the solidification profile of steel according to the carbon concentration ([C]). Many studies showed that the degree of solid-shell unevenness was large at [C] ≈ 0.1 wt%, [28][29][30][31][32] but some studies showed large solid-shell unevenness even at ultra-low [C].…”
Section: Prediction Model For Degree Of Solid-shell Unevenness During Initial Solidification In the Moldmentioning
confidence: 99%
“…The casting parameters used in this calculation are listed in Table 1. The multiphysics behaviors were solved simultaneously for a period of time to obtain the steady shell growth and slag infiltration [14]. Slag properties are determined by the combinations of individual components, and these properties evolve during the continuous casting process, especially the casting for high Mn-high Al steel due to the steel/slag reaction.…”
Section: Of 12mentioning
confidence: 99%
“…In our previous work, a numerical model that addresses the limitations of concurrent phenomena in the continuous casting mold, including fluid flow, heat transfer, shell solidification and mold oscillation, was developed [13,14]. The model was successfully used to characterize the slag infiltration phenomena and initial shell solidification during the casting process from cast-start to steady-state.…”
Section: Introductionmentioning
confidence: 99%